Comparative Analysis of K-13 and Merdeka Curriculum: A Pedagogical Approach Perspective - Subiyantoro, Singgih; Maulana, Muhammad Arief; Wulandari, Andhika Ayu; Siwi, Dwi Anggraeni (International Journal of Applied Educational Research (IJAER), 2024)
The Indonesian education system has undergone significant curricular reforms with the introduction of the 2013 Curriculum (K-13) and the Merdeka Curriculum. This study aims to conduct a comparative analysis of these curricula from a pedagogical approach perspective, examining their impacts on primary, junior, and senior high school education in Indonesia. Using a mixed-methods approach, data were collected through quantitative surveys and qualitative interviews with teachers, students, and educational policymakers across diverse regions. Results indicate that the Merdeka Curriculum is generally preferred due to its flexibility, learner autonomy, and emphasis on holistic development, which have led to improved student engagement and critical thinking skills. However, challenges such as inadequate resources and the need for better teacher training persist. The K-13, while structured, often constrained innovation and student engagement. This research contributes to the education field by providing empirical evidence on the effectiveness of these curricular reforms, offering insights for policymakers and educators to enhance curriculum design and implementation for better educational outcomes in Indonesia.